Academic Writing: Difficulties and Possible Solutions for Engineering Students - L. M. Bolsunovskaya; I. E. Rymanova (Высшее образование в России, 2020)
Academic writing is considered to be the most challenging and difficult skill in terms of English as a Second Language. This study critically explores the obstacles in academic writing faced by students at Tomsk Polytechnic University, Russia. To investigate, a comprehensive questionnaire has been floated among professional teachers to get their expert opinions (about students’ obstacles in writing) in order to identify some problems and form effective remedial strategies eventually. This paper focuses on the two significant aspects of academic writing, namely language skills (LS) (Grammar etc.) and writing skills (WS) (writing itself as a skill). Equally relevant to the issue are organization, coherence, and connectivity. The authors claim that Russian learners have poor learning background in writing skills due to the lack of balanced syllabus and teaching technologies. Aside from this, only determining problems is not sufficient to take students out of writing phobia. Furthermore, it is necessary to point out the fact that poor reading skills also lead to this kind of disappointment. Most of Russian learners do not know how to initiate their composition (essays). This paper will prove to be an academic contribution to improve the writing skills among ESL/EFL Russian learners in general and students of Tomsk Polytechnic University in particular. The presented analysis should also be of interest to researchers in other countries (universities) in which the field of academic writing is emerging.